Evaluating the optimal innovative cost control techniques used in the South African construction industry - Duku, Leju (Department of Construction Economics and Management, 2021)
The execution of construction projects commands a myriad of technological, human, organisational and natural resources. However, the construction and engineering undertaking of these projects are frequently overshadowed by economic difficulties, such as the high costs of construction materials, that have a negative impact on project costs. Cost overruns have been determined as a phenomenon continually plaguing the construction industry in both private and public sectors, and very few projects are completed within cost parameters. This research evaluated the barriers to the use of innovative cost control techniques during the construction phase, and determined the level of cost overruns on construction projects in South Africa; identified innovative cost control techniques used by construction firms on construction projects; established the optimal innovative cost control technique used in the South African construction industry; and uncovered the relationship between the level of use of innovative cost control techniques on construction projects and cost overrun. Questionnaires were the chosen instrument for data collection and were circulated via Survey Monkey. A total of 123 questionnaires were returned, and they provided the base for the computation of study results. Statistical tools employed in the study included percentages, mean item score (MIS), and frequency distributions. A scatter plot was used to distinguish whether there was a correlation between the cost performance of projects and level of innovativeness by establishing a line of best fit through the set of the two variables. A line of best fit in the positive direction indicates that increased levels of innovativeness improves the cost performance of projects, while a line of best fit in the negative direction indicates that increased levels of innovativeness does not enhance project performance. The relationship between the level of innovative cost control techniques usage in construction projects and cost overrun was determined to be negative. This led to the conclusion that construction professionals are limiting themselves and are not exploring alternative or innovative cost control techniques. They were focused on project efficiency and productivity rather than cost overruns. Innovative cost control techniques identified in the study were Earned Value Analysis (EVA), Last Planner System (LPS), 4D Scheduling, Fuzzy Project Scheduling, Integrated critical path and Line of Balance, and Reserve Analysis. Study findings determined that the critical contributors to cost overruns included tight project budgets, project complexity, a high frequency of change orders by clients and financial difficulties encountered by contractors. Perceived barriers to the implementation of innovative cost control techniques in projects by participants included a poor scope definition, a lack of training and technical skill of project personnel, poor understanding of cost analysis and variables involved in cost planning. It also emerged that projects cannot meet project objectives, and construction organisations are not making use of the right tools and techniques to monitor and control construction costs. The research findings have shown that professionals have limited knowledge of innovative cost control techniques. This also concludes that they are not taking advantage of the features of new innovative techniques to tackle complex projects. This, therefore, means that complex projects will continue to experience cost overruns. This study concludes that top management of construction organisations are not training their staff to embrace new technologies and innovation. To address the barriers to the use of innovative techniques, there should be increased investment on the part of construction organisations toward affording their workforce the relevant training, knowledge and technical skill required to implement the modern techniques for cost control identified in the report. The cidb should organise seminars and workshops on the usefulness and importance of innovative cost control techniques, and workers should embrace self-development and change. Government should implement policies on the use of innovative cost control techniques for their projects, and construction organisations should develop capacity in line with innovative cost control techniques.